MicroRNA199a-Based Post-transcriptional Detargeting of Gene Vectors for Hepatocellular Carcinoma - Bijay Dhungel; Charmaine A. Ramlogan-Steel; Christopher J. Layton; Jason C. Steel (Elsevier, 2018)
A gene therapeutic platform needs to be both efficient and safe. The criterion of safety is particularly important for diseases like hepatocellular carcinoma (HCC), which develop in a background of an already compromised liver. Gene vectors can be constructed either by targeting HCC or by detargeting liver and/or other major organs. miRNA-based negative detargeting has gained considerable attention in recent times due to its effectiveness and the ease with which it can be adapted into current gene delivery vectors. In this study, we provide a proof-of-concept using miRNA199a as a negative targeting agent. We introduced vectors harboring reporters with miRNA199a binding sites in cells expressing high endogenous levels of miRNA199a and compared the reporter expression in HCC cells with low endogenous miRNA199a. We observed that the expression of reporters with miRNA199a binding sites is significantly inhibited in miRNA199a-positive cells, whereas minimal effect was observed in miRNA199a-negative HCC cells. In addition, we created a post-transcriptionally regulated suicide gene therapeutic system based on cytosine deaminase (CD)/5-fluorocytosine (5-FC) exploiting miRNA199a binding sites and observed significantly lower cell death for miRNA199a-positive cells. Furthermore, we observed a decrease in the levels of miRNA199 in 3D tumorspheres of miRNA199a-positive Hepa1-6 cells and a reduction in the inhibition of reporter expression after transfection in these 3D models when compared with 2D Hepa1-6 cells. In summary, we provide evidence of miRNA199a-based post-transcriptional detargeting with relevance to HCC gene therapy. Keywords: gene therapy, post-transcriptional targeting, heptocellular carcinoma, miRNA, miRNA199a